Digital interventions for people living with non-communicable diseases in India: A systematic review of intervention studies and recommendations for future research and development. (December 2019) - Hossain, Md Mahbub; Tasnim, Samia; Sharma, Rachit; Sultana, Abida; Shaik, Araish Farzana; Faizah, Farah; Kaur, Ravneet; Uppuluri, Madhuri; Sribhashyam, Mitali; Bhattacharya, Sudip
Background: A high burden of non-communicable diseases (NCDs) is contributing to high mortality and morbidity in India. Recent advancements in digital health interventions, including mHealth, eHealth, and telemedicine, have facilitated patient-centered care for NCDs. Objective: This systematic review aims to evaluate the current evidence on digital interventions for people living with NCDs in India and the outcomes of those interventions. Methods: We adopted PRISMA guidelines and systematically reviewed articles from MEDLINE, CINAHL, PsycINFO, ERIC, and Scopus databases with following criteria: journal articles presenting digital intervention(s) used by people with at least one of the NCDs, reporting health outcomes following the intervention, studies conducted in India among Indian population. Results: Among 1669 articles retrieved from multiple sources, only 13 articles met our criteria. Most ( n = 7) studies were conducted in southern states of India; eight studies included patients with diabetes, followed by neuropsychiatric disorders and other NCDs. Five studies recruited participants from tertiary hospitals; six interventions used text-messaging for delivering health services, and 10 studies reported randomized controlled trials. All the studies reported positive health outcomes following the intervention, including better self-management, increased patient–provider communication, improved medication adherence, and reduced disease symptoms. Most studies scored moderate to high in quality assessment checklist of Downs and Black. Conclusion: Current evidence suggests a low number of interventions with positive outcomes. Future research should explore avenues of advanced technologies ensuring equitable and sustainable development of digital health interventions for people living with NCDs in India.